Hitherto unknown and poorly known morphs of Macrosiphoniella davazhamci and M. nikolajevi (Hemiptera: Aphididae)—aphid species new to Iran - Kanturski, Mariusz; Barjadze, Shalva (Zootaxa, 2018)
We present the first records from Iran of Macrosiphoniella (Asterobium) davazhamci Holman & Szelegiewicz, 1974 and M. (Ramitrichophorus) nikolajevi Kadyrbekov, 1999 (Hemiptera: Aphididae: Aphidinae) from samples collected by the late Prof. G. Remaudière. Previously, Macrosiphoniella davazhamci was known from Kazakhstan, Mongolia and China, whereas M. nikolajevi only from south Kazakhstan. The Iranian material includes hitherto unknown or poorly known morphs of those two species. We describe and illustrate for the first time the alate vivipara of M. nikolajevi and the ovipara and alate male of M. davazhamci. Additionally, we redescribe the poorly known alate vivipara of the latter species. Notes on the distribution and host plants in Iran are also provided.